Intrarenal Reflux in the Light of Contrast-Enhanced Voiding Urosonography - Simicic Majce, Ana; Arapovic, Adela; Saraga-Babic, Mirna; Vukojevic, Katarina; Benzon, Benjamin; Punda, Ante; Saraga, Marijan (Frontiers in Pediatrics, 2021)
Purpose: The aim of this study was to analyze the incidence of intrarenal reflux (IRR) among vesicoureteral refluxes (VURs), diagnosed by contrast- enhanced voiding urosonography (ceVUS), to define VUR-s which are positive to IRR and their locations in the kidney. Material and Methods: Seventy patients with VURs, including 103 uretero-renal units (URUs) with VURs of grade II-V (37 URUs were excluded because of renal anomalies or absence of VUR) were examined with ceVUS due to recurrent febrile UTI or first febrile UTI accompanied by abnormalities on renal ultrasonography. Patients were examined on GE Logiq S8 ultrasound machine, using second generation of ultrasound contrast agent. Results: Out of 103 VUR-s, 51(49.51%) had IRR regardless the grade of VUR, showing increase in IRR incidence with VUR severity (p<0.0001). The median age at the time of IRR diagnosis was 5 months (IQR- 3 to 14.3), whereas in patients without IRR it was 15.5 months (IQR- 5 to 41.5), (p=0.0069). IRR was most common in superior pole (80%), followed by inferior pole (62.7%), and middle segments (37%), and to all segments (27%) (p<0.0001). Conclusion: IRR showed significantly higher incidence by using ceVUS method compared to voiding cystourethrography (VCUG), including earlier clinical presentation of IRR associated VURs. The distribution of IRRs corresponded to natural distribution of composed papillae type II and III, while incidence of IRR increased with severity of VUR. Based on representative number of diagnosed IRRs in our study we propose that existence of IRR should be taken into consideration in the future classification of VURs.